Maqasid Sharia in Dharar Parameters During the Pandemic - Lukman Abdul Mutalib; Ahmad Misbah bin Mohamad Hilmi; Muhamad Ismail bin Abdullah; Mohd Rofaizal bin Ibhraim; Ismail bin Omar; Abdul Hakim bin Baharudin @ Ismail (Published by Human Resource Management Academic Re, 2024)
Vol. 13, No. 2, 2023, Pg. 1155 – 1164